Further evidence that Whorfian effects are stronger in the right visual field than the left - Drivonikou, G. V. (National Academy of Sciences, 2007)
The Whorf hypothesis holds that differences between languages induce differences in perception and/or cognition in their speakers. Much of the experimental work pursuing this idea has focused on the domain of color and has centered on the issue of whether linguistically coded color categories influence color discrimination. A new perspective has been cast on the debate by recent results that suggest that language influences color discrimination strongly in the right visual field but not in the left visual field (LVF). This asymmetry is likely related to the contralateral projection of visual fields to cerebral hemispheres and the specialization of the left hemisphere for language. The current study presents three independent experiments that replicate and extend these earlier results by using different tasks and testing across different color category boundaries. Our results differ in one respect: although we find that Whorfian effects on color are stronger for stimuli in the right visual field than in the LVF, we find that there are significant category effects in the LVF as well. The origin of the significant category effect in the LVF is considered, and two factors that might account for the pattern of results are proposed.